Drug utilization study of antiparkinsonian medication in Romania during 25 years - Bucsa, Camelia; Bruhs, Denisa; Apan, Anamaria; Francu, Elena; Mogosan, Cristina; Iaru, Irina (Frontiers in Pharmacology, 2025)
BackgroundAntiparkinsonian medication has significantly evolved over the last 2 decades, offering various pharmacologic approaches. The aim of this study was to explore the trends and to determine the statistical significance of the observed changes in the antiparkinsonian medication utilization in Romania during 1998–2022.MethodsThis antiparkinsonian drug utilization study used data provided by CEGEDIM Romania, originating from the Pharma and Hospital Report. Quantitative data for each ATC N04 antiparkinsonian medication were converted to total defined daily doses (DDDs) and to DDD/1000inhabitants/day (DDD/TID). The autoregressive integrated moving average (ARIMA) model was employed to determine the statistical significance of the observed changes in the trends of antiparkinsonian drug use.ResultsThe utilization of antiparkinsonian medication increased considerably (6-folds) in Romania during the 25 years, from 1.03 DDD/TID in 1998 to 6.22 DDD/TID in 2022. Starting 2005, dopamine precursor (levodopa) became the most used antiparkinsonian drug and remained on this position until the end of the study (13-fold increase from 0.17 in 1998 to 2.30 DDD/TID in 2022). MAO-B inhibitors represented the second most used antiparkinsonian drug class for the majority of the years. Selegiline was the most used until 2017 (0.82 DDD/TID), when a decrease in use was observed and continued until 2022 (0.49 DDD/TID). Utilization of dopamine agonists started in 1999, with less than 0.01 DDD/TID, and increased to 1.47 DDD/TID in 2022. Ropinirole was the most used dopamine agonist (0.56 DDD/TID in 2022). Anticholinergic agents represented the most used antiparkinsonian drugs until 2005. Trihexyphenidyl was the main anticholinergic prescribed with a maximum utilization of 0.82 DDD/TID in 2000 followed by a slight decrease until 2022 (0.56 DDD/TID). Amantadine utilization was mainly constant throughout the 25 years, with 0.32 DDD/TID prescribed in 2022. ARIMA analysis showed that the changes in antiparkinsonian drugs consumption were not statistically significant and overall, the trend for antiparkinsonian drug use demonstrates an upward trajectory.ConclusionAntiparkinsonian medication showed an increasing utilization trend in Romania during 1998–2022. Levodopa was the most used antiparkinsonian medicine after 2005, replacing anticholinergic agents. MAO-inhibitors utilization came in second and was followed by dopamine agonists. Observing the trend in antiparkinsonian medication utilization over time is essential for providing insights into their real-world use and uptake in a large population.